Bioequivalence studies of the generic quetiapine (Quantia 200(R)) and the innovator preparation (Seroquel(R)) 200 mg given orally in healthy Thai male volunteer - Kanlayanee Rattana (Prince of Songkla University, 2008)
Thesis (M.Sc., Pharmacology)--Prince of Songkla University, 2008